Evidências de validade de conteúdo de um instrumento para mensurar o uso das estratégias de aprendizagem no Ensino Médio - Galvão, Angela de Souza Lopes (2024)
Learning strategies are sequences of procedures employed in order to facilitate the acquisition, storage, and usage of information. This study aimed at developing and verifying the evidence of content validity of an instrument designed to measure the use of cognitive and metacognitive learning strategies among high school students, whether mediated by Digital Information and Communication Technologies or not. It is a psychometric study, descriptive in nature, with a quantitative approach. For it to be developed, the research was carried out in three stages a) a literature review on the database of Scopus, Educational Resources Information Center (ERIC), Scientific Electronic Library Online (SciELO), and the virtual library, Google Scholar databases, combined with data collection from high school students, who responded to a 28-item questionnaire developed by the author, based on the literature; b) the formulation of instrument items reflecting the learning strategies identified in the literature and reported by students; and c) content validation by subject matter experts, specialists, and the target population. The data were analysed by the Content Validity Coefficient (CVC). A total of 262 articles were retrieved, with two of them being analysed in depth. The questionnaire, which supported item generation, was completed by 191 students. Following the integration of theoretical data and student responses, the instrument entitled "Learning Strategies Scale with Digital Technologies Option for Secondary Education (EEATDIC-EM)" was developed, comprising 41 items. Five experts, two specialists, and 30 adolescents participated in the content validation process. The findings demonstrated high content validity indices for the instrument, with a Content Validity Coefficient of 0.98 for clarity, 0.96 for relevance, and 0.93 for comprehensiveness. It is expected that educational professionals have subsidies available for identifying learning strategies, mediated or not by digital technologies, used by high school students and that such information allows for the elaboration of pedagogic intervention which encourages the conscious and strategic use of these tools thus contributing to the development of skills such as autonomy, self-regulation, and critical thinking. Thereby, not only enhancing study practices is sought but also to improve academic performance and better equip students to face the challenges of the contemporary world.